An Analysis of the Contribution of Microteaching Course to the Teaching Skills of Students Teachers of English Language Education Study Program Batanghari University - Wennyta Wennyta (Universitas Batanghari Jambi, 2017)
AbstractThis research used 40 students of English Language Education Study Program of Faculty of Teachers Training and Education of Batanghari University Jambi year 2014 as the sample. Their Microteaching score and their supervisors’ assessment of their teaching performance in teaching practice in the form of 40 questions questionnaire were analyzed using statistical method. The result of correlation test showed that there is a positive influence of Microteaching score to the teaching skills of the students. The result of the coefficient of determination is 0.419, which means that variable Microteaching influenced the teaching skills of the students by 41.9% while the other 58.1% was influenced by other factors outside the scope of the research.Keywords: Microteaching, Student teacher, Teaching skills